2021
DOI: 10.32535/apjme.v4i2.1149
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Employee Performance in The Department of Education and Culture, Lubuklinggau City

Abstract: The aims of this research are to determine the impact of incentivizing, motivation and discipline on the performance of The Department of Education and Culture of Lubuklinggau City employees simultaneously and partially. Qualitative method was used in this research, with 57 employees at The Department of Education and Culture of Lubuklinggau City as a sample. Multiple linear regression test, coefficient of determination test, f-test and t-test were used in this research as data analysis technique. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 14 publications
(21 reference statements)
1
13
0
5
Order By: Relevance
“…The results of this study were supported by Astriyani et al(2019) Pebrianti & Simanjuntak (2020), Chebet & Njirge (2019), Hidayah & Nurbaiti (2019), Riwukore et al (2021). However, the results of this study are different from Prayitno et al (2020) and Wewengkang et al (2021).…”
Section: Hypothesis 4 (Effect Of Motivation On Employee Performance)supporting
confidence: 61%
“…The results of this study were supported by Astriyani et al(2019) Pebrianti & Simanjuntak (2020), Chebet & Njirge (2019), Hidayah & Nurbaiti (2019), Riwukore et al (2021). However, the results of this study are different from Prayitno et al (2020) and Wewengkang et al (2021).…”
Section: Hypothesis 4 (Effect Of Motivation On Employee Performance)supporting
confidence: 61%
“…The research reported by Dame et al (2021) that the variables of discipline, motivation, and organizational commitment have a positive and significant influence together on employee performance at Bank Prisma Dana North Sulawesi. Likewise reported by Riwukore et al (2021a) that motivation and discipline have a positive and significant influence on employee perfor-mance at the Education and Culture Office of Lubuklinggau City.…”
Section: The Effect Of Discipline Motivation and Organizational Commi...mentioning
confidence: 94%
“…If there is no clear pattern, the points spread above and below zero on the Y axis, then there is no heteroscedasticity. In addition, heteroscedasticity can be known through the Glesjer test, where if the significance probability of each independent variable is > 0.05, it can be concluded that there is no heteroscedasticity in the regression model (Riwukore et al, 2021a). The heteroscedasticity test in this study used the Glesjer test as presented in Table 4.…”
Section: B Heteroscedasticity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sugianto (2012) op.cit. Riwukore, Susanto, Pilkandis, et al (2021) that a good regression model has a data distribution that is normal or close to normal. To test it by looking at the normal probability plot which compares the cumulative distribution of the actual data with the cumulative distribution of the normal distribution.…”
Section: B Heteroscedasticity Testmentioning
confidence: 99%